(untitled) (GEOAREA | Jurnal Geografi, 2025)
Coffee is a commodity with high economic value, especially in Pangalengan District. The success of coffee cultivation requires an analysis of the factors that support the suitability of land for coffee cultivation. The data analysis method used for land evaluation is a matching method between land suitability parameters and coffee plant growth requirements, with soil samples taken through field surveys in the three sample villages, namely Margamulya Village, Pangalengan Village, and Warnasari Village. Spatial data was overlaid to produce a land suitability map to map the classification of land suitability classes. The results and conclusions of this study show that Pangalengan District, Bandung Regency, especially the sample areas of the three villages, are classified as highly suitable (S1) 37.60%, moderately suitable (S2) 47.64%, marginally suitable (S3) 13.79%, and unsuitable (N) 0.98%. These areas have favorable climate and soil conditions, such as temperature, rainfall, altitude, slope, effective soil depth, good drainage, and high nutrient content, which are ideal for the growth of Arabica coffee varieties with minor constraints that can still be managed. Robusta varieties can also still grow, albeit to a limited extent. Amelioration measures such as the application of organic and inorganic fertilizers are needed to improve soil quality and fertility. The research results can be compiled into teaching modules for geography in high schools.